Carboxymethyl Cellulose/Poly(Acrylamide-co-Vinyl Imidazole) Based Self-healing Hydrogel for Supercapacitor Applications and Moisture Determination (Part-II) (Journal of Scientific Research, 2024)
Physical entanglements between carboxymethyl cellulose chains and poly(acrylamide-co-vinyl imidazole) have resulted in a unique solid hydrogel electrolyte (SHE) material with highly controllable properties. The SHE showed an excellent self-healing property, as confirmed by the "LED glowing" experiment, and the 'self-healed 'material recovered 78 % of its original elongation capacity. The freshly prepared SHE, when put on the copper surface, required a detachment pressure (DP) of 864 Pa, while a fairly high DP of 8909 Pa was required after 24 h of contact. The SHE sample was highly flexible and regained its shape after knotting, folding, and twisting. The hydrogel also exhibited shape memory property. Finally, the samples SHE-I   and SHE-IV (containing 0 and 4 mL glycerol per 40 mL of film forming solution) were charged using a 12-volt supercapacitor for 2 min and then employed to glow LED bulb as well as run alarm clock. It was found that sample SHE-I was able to glow the LED bulb for almost 55 min, while sample SHE-IV successfully lit the LED for almost 357 min. Similarly, a small alarm clock was run by the two SHE systems for 118 and 838 min, respectively.